Langerhans Cell Histiocytosis – A Challenge for the Dental Professional - Bansal, Shweta (J Cutan Aesthet Surg, 2017)
Langerhans cell histiocytosis (LCH) is a group of rare disorders histologically characterized by the proliferation of LC, involving multiple organs and systems. Typically, there is bone involvement and, less frequently, lesions may be found in the lungs, liver, lymph nodes, skin, and mucosae. Oral soft tissue lesions without bone involvement are rare. Antigenic markers that react with CD1a glycoprotein, cytoplasmatic protein S100 detected by immunoperoxidase staining, and/or presence of Birbeck granules on electron microscopic examination are required for a definitive diagnosis of LCH. In this article, we report a case of LCH, which had presented with multiple oral lesions without any other systemic signs and symptoms. Management of such children with periodontal manifestations should include hematological and, if possible, immunological investigations at an early stage. Careful clinical examination, good diagnostic skill, and awareness of characteristic cytological features of LCH can lead to earlier diagnosis and treatment with minimal deformity.